Hug each other, not the trees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
'Our country is losing 1% of its dry forest areas each year, at a rate of 100,000 hectares' declared the Minister for Higher Education and Scientific Research of Benin at the opening of the international workshop on 'Integrated management of natural...